Docking Studies to Predict the Effectiveness of Novel Fluoroquinolone Molecules against Topoisomerase of Vibrio Cholerae. - Kaur, Sukhmanpreet (My University, 2017)
Vibrio cholera, the causative agent of Cholera is responsible approximately 21,000 to 143,000 deaths worldwide. One of the treatments for the disease involves use of broad spectrum antibiotic fluoroquinolone, ciprofloxacin, that acts by seizing topoisomerase activity thus preventing the DNA replication in the bacteria. In 2002, there were reports of reemergence of the Vibrio cholera strains that was considered eliminated from the face of earth in 1987. The genome analysis of the recent strains proved that newly emerged strains are resistant to present fluoroquinolones due to mutation in the gyrA, gyrB, parC and parE genes. These genes are responsible for the topoisomerase II (topo-II). This dissertation is a dry lab approach to understand the interactions between the mutated topoisomerase structures with the different fluoroquinolone based ligands with the help of docking studies using AutoDoc Vina 4.0. This study proposes and concludes that RG-1, RG-2 and RG-3 ligands exhibits better binding energies than ciprofloxacin against mutant topo-II.
Keywords: Levofloxacin; Muscle; Blast; Swissmodel; EMBL-EBI; QRDR